2022
DOI: 10.1002/dac.5199
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation of super‐wideband 8‐port Multiple‐Input‐Multiple‐Output antenna with high isolation for future wireless applications including Internet of Things

Abstract: SummaryThe paper reports an experimental investigation of an 8 × 8 MIMO antenna fabricated on a commercially available FR4 substrate. A fractal printed monopole radiator is introduced as a good prospect for super‐wideband (2.85–20.0 GHz) multiple‐input‐multiple‐output (SWB‐MIMO) configuration. The MIMO antenna is printed on both the planes (Plane A and Plane B) where four antennas are printed on Plane A and remaining on Plane B which are fed asymmetric to achieve wider impedance bandwidth. An inverted‐L type s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…A super wideband antenna with four notched bands offers operational bandwidth of 1.15GHz-40.0GHz and maintains isolation by arranging the truncated elliptical self-complimentary patch in an orthogonal fashion [20]. 8-port narrow-band (5G applications) [25] and super wideband [26] utilizes flowershaped patch with side L-shaped stub attached to the ground providing maximum radiation in the desired direction. A review on the conformal antenna is reported [27], [28], [29] which utilizes substrates such as PET, and thin Rogers substrate for bending of antenna applications.…”
Section: Introductionmentioning
confidence: 99%
“…A super wideband antenna with four notched bands offers operational bandwidth of 1.15GHz-40.0GHz and maintains isolation by arranging the truncated elliptical self-complimentary patch in an orthogonal fashion [20]. 8-port narrow-band (5G applications) [25] and super wideband [26] utilizes flowershaped patch with side L-shaped stub attached to the ground providing maximum radiation in the desired direction. A review on the conformal antenna is reported [27], [28], [29] which utilizes substrates such as PET, and thin Rogers substrate for bending of antenna applications.…”
Section: Introductionmentioning
confidence: 99%